Hajj Financing Models: Fiqh Analysis of Payment Contracts for Hajj Funds at the Ministry of Religious Affairs in Indonesia - Jamal, Mulyono; Zahro', Khurun'in; Nugraheni, Nuriwanda Azizah; Cahyo, Eko Nur (Universitas Islam Sultan Agung, 2024)
Hajj is an act of worship that completes the fifth pillar of Islam for a Muslim and is performed by those who are able. In its implementation in Indonesia, the hajj is organised by the Ministry of Religious Affairs (MORA) of Republic of Indonesia, including the offices of MORA in every city throughout Indonesia. The contract used during the registration of prospective pilgrims is a wakalah contract, but when they attend to the bank, the bank requestions what kind of contract will be employed whether wadi'ah or murabahah. This research is purposed to reveal the repayment contract for prospective pilgrims and analyse the principle of the contract applied in the repayment of funds for prospective pilgrims. The type of research used is field research with qualitative methods using descriptive analysis. The primary data sources in this research are obtained from the MORA of the Republic of Indonesia, while the secondary data was attained from journals or research related to the hajj financing model, then descriptive analysis of the data as material for the research findings. There are two findings in this research, firstly, the contract on the repayment of funds for prospective pilgrims, starting from the wakalah contract between prospective pilgrims and the MORA, this contract will take effect after the repayment of funds for prospective pilgrims. Secondly, the fiqh analysis of the principle of the contract applied to the repayment of funds for prospective pilgrims is wakalah and is appropriate as it should be. Even so, the MORA must also cooperate with stakeholders in providing the best service to hajj pilgrims so that they can perform the worship in holy lands (Madina and Mecca) comfortably and solemnly.